2016
DOI: 10.1007/s10753-016-0494-0
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from iPSCs Delivering siRNA Attenuate Intracellular Adhesion Molecule-1 Expression and Neutrophils Adhesion in Pulmonary Microvascular Endothelial Cells

Abstract: The pro-inflammatory activation of pulmonary microvascular endothelial cells resulting in continuous expression of cellular adhesion molecules, and subsequently recruiting primed neutrophils to form a firm neutrophils-endothelium (PMN-EC) adhesion, has been examined and found to play a vital role in acute lung injury (ALI). RNA interference (RNAi) is a cellular process through harnessing a natural pathway silencing target gene based on recognition and subsequent degradation of specific mRNA sequences. It opens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…This method is widely accepted in the studies on the exosomes. 5,11,26,27 Previous study using nanoparticle tracking analysis showed that TNFα did not alter the size distribution of the exosomes, 11 suggesting that the protein content is well related to the enumeration (concentration) of the exosomes. However, the exosomes should be ideally counted by a particle analyzer, although a high cost for the instruments including nanoparticle tracking analysis or high-resolution flow cytometer restricts their use in exosomes-related studies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This method is widely accepted in the studies on the exosomes. 5,11,26,27 Previous study using nanoparticle tracking analysis showed that TNFα did not alter the size distribution of the exosomes, 11 suggesting that the protein content is well related to the enumeration (concentration) of the exosomes. However, the exosomes should be ideally counted by a particle analyzer, although a high cost for the instruments including nanoparticle tracking analysis or high-resolution flow cytometer restricts their use in exosomes-related studies.…”
Section: Discussionmentioning
confidence: 96%
“…In the current study, we used the protein content of the exosomes to represent the concentration of exosomes. This method is widely accepted in the studies on the exosomes . Previous study using nanoparticle tracking analysis showed that TNF‐α did not alter the size distribution of the exosomes, suggesting that the protein content is well related to the enumeration (concentration) of the exosomes.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse models of lung injury, mesenchymal stromal cell extracellular vesicles have similar efficacy to mesenchymal stromal cells themselves. Finally, exogenous extracellular vesicles could be modified to package custom drugs or protective RNA cargo, which could be delivered to specific cell types as determined by the extracellular vesicle surface markers [47].…”
Section: Clinical Applications For Extracellular Vesicles In Ardsmentioning
confidence: 99%
“…siRNA loading is similar to that of miRNA loading, with electroporation being the most common method of active loading [209]. In a model of acute lung injury, EVs isolated from iPSCs derived by reprogramming renal epithelial cells were subjected to electroporation to introduce siRNA against ICAM-1, which is involved in the inflammatory response [210].…”
Section: Evs As a Cargo Delivery Systemmentioning
confidence: 99%